PERANAN LEVERAGE DAN PROFITABILITAS TERHADAP SUSTAINABLE GROWTH: STUDI PADA SEKTOR MANUFAKTUR DI BEI - Chandradinangga, Arinta; Rita, Maria Rio (International Journal of Social Science and Business, 2020)
The study of sustainability has attracted the interest of some researchers lately, both at the level of small businesses and corporate. Sustainable growth is one measure of good company performance because it combines operating and financial policies. Companies that have high debts are not always bad, but they need supervision and planning so as to produce optimal decisions for the company. This study aims to analyse the effect of leverage and profitability on sustainable growth in manufacturing sector companies in 2015-2017 which are listed on the Indonesia Stock Exchange (IDX). The purposive sampling approach was used in the selection of samples, and obtained as many as 70 companies in accordance with existing criteria. This study uses multiple linear regression analysis to process the data. This study proves that leverage has a significant positive effect on sustainable growth, while profitability has a significant positive effect on sustainable growth.